2022
DOI: 10.3390/ani12081009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Somatic Cell Score in Florida Goats Using Single and Multiple Traits Models

Abstract: A total of 1,031,143 records of daily dairy control test of Spanish Florida goats were used for this study. The database was edited, and only the records of the first three lactations were kept. The final database contained 340,654 daily-test somatic cell counts from 27,749 daughters of 941 males and 16,243 goats. The evolution of this count in the last 14 years was analyzed following French and American international associations’ criteria for the risk of mastitis in goats, and confirmed the slight increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In this breed, Jiménez-Granado et al [7] showed how the levels of this parameter have increased alarmingly over the last decade, which is consistent with the levels of mastitis perceived by the farmer. It is therefore considered necessary to establish a plan to control and prevent mastitis, which combines sanitary and management measures with the search for greater resistance to this disease.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In this breed, Jiménez-Granado et al [7] showed how the levels of this parameter have increased alarmingly over the last decade, which is consistent with the levels of mastitis perceived by the farmer. It is therefore considered necessary to establish a plan to control and prevent mastitis, which combines sanitary and management measures with the search for greater resistance to this disease.…”
Section: Introductionsupporting
confidence: 69%
“…A recent publication indicates that cumulative milk production in the period up to 240 days of lactation in the Florida breed has increased at a rate of 1.7% per year. However, this may, as a collateral effect, have increased potential infection problems, which is reflected in aspects such as somatic cell count (SCC), due to the constant interaction between the udder and the milking equipment [7]. Although a certain level of SCC may be tolerated as an indicator of resistance to infection, immunity and health, it may also represent risks to product quality and could result in economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, DNAJC18 was located within the ROHi located in CHI7. Despite its function has not yet been reported in goats, it was related to heat stress resistance in cattle (Hu et al, 2020), a well‐known characteristic of Florida goats, that is, well‐adapted individuals to the hot temperatures and harsh environments in their area of influence in the south of Spain (Jimenez‐Granado et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current breed census includes 28,243 individuals (27,423 dams and 820 bucks) located in 81 herds distributed in 14 Spanish provinces. The breeding programme was developed by the Asociación de Criadores de Cabra Florida (ACRIFLOR) and is mostly focused on selecting fertile individuals which can produce milk under the semi‐intensive harsh productive conditions of the Iberian Peninsula (extensive pasturelands and hot weather) (Jimenez‐Granado et al, 2022; Ziadi et al, 2021). The analysis of inbreeding levels in the Florida goat breed using molecular data is still missing and would be therefore of great interest to develop its breeding programme.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the breeding programmes for Spanish dairy goats are generally focused on improving milk production and milk composition traits (Menéndez‐Buxadera et al, 2010; Molina et al, 2018), or somatic cell score (Jimenez‐Granado et al, 2022), on morphological, and more recently, reproductive traits (Ziadi, Muñoz‐Mejías, Sánchez, et al, 2021; Ziadi, Muñoz‐Mejías, Sánchez Rodríguez, et al, 2021). However, the undesirable consequences have been widely reported of selection for high milk production on the health and fertility of animals, which decreases longevity (Oltenacu & Broom, 2010).…”
Section: Introductionmentioning
confidence: 99%